2010
DOI: 10.1111/j.1750-3841.2009.01386.x
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose Reinforced Chitosan Composite Films as Affected by Nanofiller Loading and Plasticizer Content

Abstract: Chitosan is a biodegradable polymer which may be used to elaborate edible films or coatings to enhance shelf life of foods. This study demonstrates how cellulose nanofibers (CNF) can improve the mechanical and water vapor barrier properties of chitosan films. A nanocomposite film with 15% CNF and plasticized with 18% glycerol was comparable to some synthetic polymers in terms of strength and stiffness, but with poorer elongation and water vapor barrier, indicating that they can be used for applications that do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
158
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(182 citation statements)
references
References 50 publications
19
158
0
5
Order By: Relevance
“…These results showed the efficiency of glycerol as a plasticizer, which was also proved in studies for films manufactured with starch by Shimazu et al (2007), with lactoglobulin by Sothornvit and Krochta (2001) and with soy protein by Cho and Rhee (2002). Azeredo et al (2010) have demonstrated that lower concentrations of glycerol and higher concentrations of commercial cellulose nanocrystals provide an increase in the mechanic properties of the films obtained from chitosan. According to the Pareto graph (Figure 3), the concentrations of glycerol (X 2 ) and nanocellulose (X 3 ) exerted a higher effect on the maximum tension value, whereas the linear interactions between glycerol (X 2 ) and nanocellulose (X 3 ) (2Lby3L), and starch (X 1 ) and nanocellulose (X 3 ) (1Lby3L) were the primary factors responsible for the deformation percentage (elongation) of the nano-biocomposites.…”
Section: Mechanical Properties Of the Filmssupporting
confidence: 67%
“…These results showed the efficiency of glycerol as a plasticizer, which was also proved in studies for films manufactured with starch by Shimazu et al (2007), with lactoglobulin by Sothornvit and Krochta (2001) and with soy protein by Cho and Rhee (2002). Azeredo et al (2010) have demonstrated that lower concentrations of glycerol and higher concentrations of commercial cellulose nanocrystals provide an increase in the mechanic properties of the films obtained from chitosan. According to the Pareto graph (Figure 3), the concentrations of glycerol (X 2 ) and nanocellulose (X 3 ) exerted a higher effect on the maximum tension value, whereas the linear interactions between glycerol (X 2 ) and nanocellulose (X 3 ) (2Lby3L), and starch (X 1 ) and nanocellulose (X 3 ) (1Lby3L) were the primary factors responsible for the deformation percentage (elongation) of the nano-biocomposites.…”
Section: Mechanical Properties Of the Filmssupporting
confidence: 67%
“…Alternatively, lowering the mechanical properties with increasing loading of filler was a consequence of agglomeration of CNC and heterogeneous size distribution. Noted decrease in EB is characteristic for nanocomposites and is a result of rigid nature of the filler and strong interactions between components of composite, responsible for restriction of the matrix motion [59,60]. Not only Atef et al but other research groups [61,62] too showed that due to good dispersion, low content of nanofiller (CNC) in polymer matrix (polylactide) is the best in terms of enhancement of mechanical properties.…”
Section: Mechanical and Morphological Properties Of Compositesmentioning
confidence: 99%
“…Thus, a microfibril can be considered as a string of whiskers linked by amorphous domains, which are taken as structural defects. Our group has studied the influence of cellulose nanofibers on the physical properties of mango puree edible films (Azeredo et al, 2009) and chitosan films (Azeredo et al, 2010). In our first study (Azeredo et al, 2009), different concentrations of cellulose nanofibers (Novacel® PH-101, provided by FMC BioPolymer, Philadelphia, PA, USA) were added to mango puree edible films.…”
Section: Cellulose Nanoreinforcementsmentioning
confidence: 99%
“…According to Helbert et al (1996), the great effect of CNRs on modulus is ascribed not only to the geometry and stiffness of the fillers, but also to the formation of a fibrillar network within the polymer matrix, the CNRs being probably linked through hydrogen bonds. In our second study (Azeredo et al, 2010), nanocomposite films were also obtained from a c h i t o s a n m a t r i x w i t h C N R s ( Figure 3 presents the contour plots for the physical properties of the nanocomposite chitosan films as functions of the CNR and glycerol concentrations. The nanofillers increased the overall tensile properties of the films, but decreased their elongation.…”
Section: Cellulose Nanoreinforcementsmentioning
confidence: 99%